6 Gene transcriptional profiles and epigenetic regulation in the development of human heart disease. (16th October 2019) - Kerrigan, L; Glezeva, N; Collier, P; Moreavec, C; Baugh, J; Ledwidge, M; McDonald, K; Das, S; Watson, C
Abstract : Heart failure (HF) has reached epidemic proportions, affecting approximately 26 million people worldwide. HF is a clinical condition in which structural and/or functional impairment in the heart mitigates its ability to adequately fill up or eject sufficient blood in order to sustain the metabolic requirements of the body. This occurs due to alterations in the size, shape or structure of the heart. HF subgroups are categorised according to the pathological changes through which HF has occurred. Epigenetic regulation has been reported to have a crucial role in development of structural alterations associated with HF. DNA methylation is the most common epigenetic modification and occurs when a methyl group is added to a cytosine within a CpG dinucleotide site. This prevents binding of transcription factors to the DNA resulting in gene repression. In previous studies, it was shown that pro-fibrotic changes in human primary cardiac fibroblasts were associated with global DNA hypermethylation. Also, inhibition of DNA methylation resulted in anti-fibrotic and anti-hypertrophic activity. The aim of this study was to investigate the impact of differential DNA methylation on gene expression profiles in HF patients. Furthermore, we aimed to study the pathological relevance of methylation-sensitive genes and determine if they can be altered using epigenetic modifying therapy. RNA sequencing and whole genome methylation profiling was carried out on cardiac tissue from HF patients diagnosed with dilated cardiomyopathy (DCM), hypertrophic obstructive cardiomyopathy (HOCM), ischemic cardiomyopathy (ISCM) and left-ventricular hypertrophy (LVH), and then compared with non-HF tissue. Genes that were highlighted as both differentially expressed and differentially methylated were selected as target candidates for in vitro validation. Human cardiac fibroblasts were cultured in normoxic and hypoxic environments, in the presence or absence of the DNA methylating inhibitor, 5-azacytidine-DC (5-AZA). Expression of selected target gene candidates were then measured. Our results show that in a PCA plot evaluating the relationship between gene expression patterns in the 4 HF subgroups compared with non-HF, there is definitive clustering between non-HF and DCM, HOCM and ISCM, but not between non-HF and LVH. We identified several target gene candidates that were both differentially expressed and differentially methylated in HF as well as being attributed to having potential pathological roles relevant to the development of heart disease. We then showed that expression of these genes is altered in hypoxic conditions, but can be manipulated by 5-AZA treatment. This study presents evidence to support the role of aberrant DNA methylation in the development of human heart disease as well as revealing novel genes that could not only pose as prospective diagnostic biomarkers for HF, but could also be potential epigenome-influencing therapeutic targets.